Comparative Evaluation of Physical Surface Changes and Incidence of Separation in Rotary Nickel-Titanium Instruments: An in Vitro SEM Study - Kaul, Rudra; Farooq, Riyaz; Kaul, Vibhuti; Khateeb, Shafayat Ullah; Purra, Aamir Rashid; Mahajan, Roopali (Iranian Endodontic Journal, 2014)
Introduction: The aim of the present study was to comparatively evaluate the physical surface changes and incidence of separation in rotary nickel-titanium (NiTi) instruments using scanning electron microscope (SEM). Methods and Materials: A total number of 210 freshly extracted human maxillary and mandibular first molars were selected and distributed between three groups. Three different systems of rotary NiTi instruments, namely ProFile (PF), RaCe (RC) and Twisted File (TF), were used to prepare the canals using crown-down technique. All instruments were evaluated by means of SEM with 500× and 1500× magnifications, at four different stages; before use, after preparation of 7 and 14 canals and after instrument separation. Photomicrographs were also taken. The data was analyzed using the Kruskal-Wallis test and the level of significance was set at 0.001. It was found that H (HAT matrix) was 15.316 with 2 degrees of freedom. Moreover the various groups were compared using the Student-Newman-Keuls test with P<0.05 and it was found that all groups were significantly different. Results: RC showed the maximum wear of the surface followed by TF (P<0.05). PF showed the minimum wear except for its tip. There was no correlation between electropolishing and file fracture. Insignificant difference was observed in the mean number of canals shaped by PF and TF before their separation. Conclusion: Clinically, TF performance was superior, followed by PF then RC. RC fracture rate was the greatest after preparing the least number of canals.